A Generalized S.M.A.C. Function with Constant Ratios of Elasticity of Substitution - Mukerji, V. (Review of Economic Studies, 1963)
Journal Article A Generalized S.M.A.C. Function with Constant Ratios of Elasticity of Substitution Get access V. Mukerji V. Mukerji Poona Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 3, October 1963, Pages 233–236, https://doi.org/10.2307/2296324 Published: 01 October 1963